Effect of vocabulary learning strategies on students’ vocabulary knowledge achievement and motivation: the case of grade 11 high school students - Ayana, Haimanot; Mereba, Temesgen; Alemu, Adege (Frontiers in Education, 2024)
Introduction-Vocabulary knowledge achievement is crucial for effective language learning. However, there is a gap in vocabulary knowledge achievement, particularly at the Seto High School in Ethiopia. This study addresses this gap by focusing on Grade Eleven students and investigating the effect of vocabulary learning strategies on students' vocabulary knowledge achievement and motivation.Eleven students, with 30 students in the experimental group and 30 in the control group, selected through convenience sampling. A mixed-method research design was also used to gather comprehensive data. The data collected included pretest and posttest assessments of vocabulary knowledge achievement, a vocabulary learning strategies (VLS) questionnaire, and semi structured interviews. The analysis of the data utilized statistical methods such as means, standard deviations, independent t -tests, and correlations to evaluate the effects of vocabulary learning strategies on students' vocabulary knowledge achievement and motivation.Results -High reliability was observed for both the VLS questionnaire and the tests. Pretest results revealed no significant (p > 0.05) difference in vocabulary knowledge achievement between the experimental and control groups. Posttest results demonstrated a statistically significant (p < 0.05) improvement in vocabulary achievement in the experimental group compared to the control group. Correlation analysis revealed a positive and significant (p < 0.05) association between VLS use and vocabulary knowledge achievement. Survey results and qualitative data showed that students predominantly relied on dictionary-based vocabulary, saying the new word aloud, using the vocabulary section in textbook, and continuing to study words over time vocabulary learning strategies before training, with a noticeable shift toward increased use of guessing, keyword, and semantic mapping strategies after training. These findings underscore the effectiveness of VLS training in enhancing vocabulary knowledge among Grade Eleven students. Finally, some recommendations are proposed.The study concluded that training in vocabulary learning strategies had a significant impact on students' vocabulary knowledge achievement.